Mapping Indo-European anatomical terminology III: Latvian mēle ‘tongue’ - Blažek, Václav (Baltistica, 2023)
In the present study Latvian mēle ‘tongue’, an isolate within the Baltic lexicon, is studied from the point of view of its etymology. The existing etymological attempts operate with the semantic development ‘speech’ → ‘language’ → ‘tongue’, which is naturally quite legitimate, but in the three concrete cases analyzed here is not convincing enough. The new solution connects Latvian mēle ‘tongue’, reflecting Proto-Baltic *mēlii̯ā, with another isolate in the Indo-European anatomical lexicon, Common Tocharian *mele- ‘nose’, reflecting Pre-Tocharian *molo- or *mēlo-. The semantic connection between ‘tongue’ and ‘nose’ is not trivial, but there are strong arguments for its acceptance, if ‘tongue’ is interpreted as ‘taster’ and ‘nose’ is interpreted as ‘smeller’.